Using Data to Advance Learning Outcomes in Schools. (October 2013) - VanDerHeyden, Amanda; Harvey, Mark
This article describes the emergence and influence of evidence-based practice and data-based decision making in educational systems. Increasingly, educators and consumers want to know that resources allocated to educational efforts yield strong effects for all learners. This trend is reflected by the widespread influence of evidence-based practice (EBP) in education and the demand for data-based decision-making models like response to intervention (RtI). This article describes the ways in which EBP and RtI can be used to improve efficacy, efficiency, and equity of educational services. The article concludes with concrete recommendations for implementing RtI.